Perancangan Sistem Suplai Tanpa Penambahan Tempat di PT Toyota Motor Manufacturing Indonesia (PT TMMIN) - Christianto Felix Juwono Suganda; I Gede Agus Widyadana; Herry Christian Palit (Jurnal Titra, 2014)
PT Toyota Motor Manufacturing Indonesia (PT TMMIN) in 2014 is preparing the implementation of new engine type TR-Kai. Additional types of engine TR-Kai need additional type of new components too. Additional types of TR-Kai component means need additional space for placement, but the problem is unavailable space. The supply system design method includes layout change, equipment (material handling) and also system (works cycle) which is delivered well. The countermeasure idea is to change the material handling usage and also implementation direct supply system. Direct supply system in regular working time has reduced lead time almost 2 days of safety stock. Direct supply reduces 33.3% of inefficient handling, reduce hoist usage (safety matter) between 80,2% up to 93.4% each day, and also reduce 81.5% of forklift usage (safety matter). The evaluation result of this system is able to reduce 33.3% of manpower supply and monthly cost saving up to 46.2% with a Break Event Point (BEP) during 4 years 7.5 months.